EFEKTIFITAS PENERAPAN BLENDED LEARNING DALAM MENINGKATKAN MOTIVASI BELAJAR MAHASISWA SASTRA INGGRIS UNIVERSITAS KHAIRUN - Magfirah, Sulmi (Interference: Journal of Language, Literature, and Linguistics, 2020)
Abstract. Blended learning is a learning model that lecturers can apply to optimize the learning outcomes. This study, entitled "The Effectiveness of Blended Learning to Increase Student Motivation" aims to determine the extent of the effectiveness of Blended Learning in increasing the learning motivation on the first semester students of the English Literature Study Program at Khairun University. This research was carried out at the English Literature Study Program a quasi-experimental study designed on using the non-equivalent control group design. A total of 50 on the first semester students were sampled in this study. The sample was divided into 2 classes, experimental class used blended learning and the control class used face-to-face learning, each consisted of 25 students. The learning motivation questionnaire was used as the instrument in collecting the data related to students learning motivation. The results showed that there were significant differences between students learning motivation in the experimental class and students in the control class after had been given different treatments. The researcher also found that the application of Blended Learning was effective in increasing the learning motivation of the first semester students of English Literature Study Program at Khairun University.